Influencing Moral Behavior Through Mere Observation of Robot Work: Video-based Survey on Littering Behavior - Maeda, Risa; Brscic, Drazen; Kanda, Takayuki (2021 16th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2021)
Can robots influence the moral behavior of humans by simply doing their job? Robots have been considered as replacement for humans in repetitive jobs in public spaces, but what could that mean for the behavior of the surrounding people is not known. In this work we were interested to see how people change their behavior when they observe either a robot or a person do a morally-laden task. In particular, we studied the influence of seeing a robot or a human picking up and discarding garbage on the observer's willingness to litter or to pick up garbage. The study was done as a video-based survey. Results show that while observing a person clean up does make people less keen to litter, this effect is not present when people watch a robot doing the same action. Moreover, people appear to feel less guilty about littering if they observed a robot doing the cleaning up than in the case when they watched a human cleaner. CCS CONCEPTS*. Human-centered computing → Empirical studies in HCI; * Computer systems organization → Robotics.